2018
DOI: 10.1021/acsami.8b05298
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Conductivity of Anion-Exchange Membrane by Incorporation of Quaternized Cellulose Nanocrystal

Abstract: High ion conductivity of anion-exchange membrane is essential for the operation of alkaline anion-exchange membrane fuel cell. In this work, we demonstrated an effective strategy to enhance the conductivity of anion-exchange membrane (AEM), by incorporation of quaternized cellulose nanocrystal (QCNC) for the first time. Morphology observation demonstrated a uniform distribution of QCNC within QPPO matrix, as well as a clear QCNC network, which led to significant enhancement in hydroxide conductivities of compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 57 publications
3
38
0
Order By: Relevance
“…An H 2 /O 2 single cell containing such a membrane yielded a power density of 630 mW cm À2 at 60 C with PtRu/C anodes, Pt/C cathodes and polysulfone ionomer (feeds with 100% relative humidity and no backpressure). The performances of some natural based AEMs have also been studied, including a composite membrane from 2 wt% quaternised CNC and quaternised PPO, which was prepared by Cheng et al 139 The H 2 / O 2 cell performance of such a membrane showed an impressive peak power density of 392 mW cm À2 at 60 C with no backpressure on the feed gases and a Pt/C cathode and PtRu/C anode. Zhou et al 121 fabricated a novel OH À conducting membrane composed of CS, an ionised organic compound and hydroxylated multiwalled carbon nanotubes cross-linked by glutaraldehyde.…”
Section: /Shementioning
confidence: 99%
“…An H 2 /O 2 single cell containing such a membrane yielded a power density of 630 mW cm À2 at 60 C with PtRu/C anodes, Pt/C cathodes and polysulfone ionomer (feeds with 100% relative humidity and no backpressure). The performances of some natural based AEMs have also been studied, including a composite membrane from 2 wt% quaternised CNC and quaternised PPO, which was prepared by Cheng et al 139 The H 2 / O 2 cell performance of such a membrane showed an impressive peak power density of 392 mW cm À2 at 60 C with no backpressure on the feed gases and a Pt/C cathode and PtRu/C anode. Zhou et al 121 fabricated a novel OH À conducting membrane composed of CS, an ionised organic compound and hydroxylated multiwalled carbon nanotubes cross-linked by glutaraldehyde.…”
Section: /Shementioning
confidence: 99%
“…Thus, FeNx-CNTs catalyst (see the synthesis and properties as Figure S6) was adopted as ORR catalyst for H 2 /O 2 fuel cell performance, with an~40 μm PVA-1.8PVBMP membrane, and the data are demonstrated in Figure 7. The water uptake of the as-made IPN AEMs was relatively high; in order to improve the oxygen transfer efficiency, gas diffusion electrode (GDE) with a better gas diffusion channel was adopted to make membrane electrode assembly (MEA); PtRu/C and FeNx-CNTs were sprayed onto anode (0.4 mg cm -2 ) and cathode (2 mg cm -2 ) carbon paper, respectively, both with 20wt% quaternized poly(2,6-dimethyl-1,4-phenylene oxide (QPPO) [46] (see the detail preparation and characterization as Figure S7 and Table S2) 5 Research quite low gas permeability. After a backpressure of 0.1 MPa was applied, the peak power density reached as high as 1.20 W cm -2 .…”
Section: Single Cell Performancementioning
confidence: 99%
“…IEC was determined using the titration method. 20 Briey, membrane samples were rstly immersed in 1 M HCl solution to convert the Li + form into the H + form. Next, the samples were washed thoroughly with water and then immersed in 2 M NaCl solution to convert the H + form into the Na + form.…”
Section: Membrane Characterizationmentioning
confidence: 99%
“…[17][18][19] In order to meet the growing requirements for IEMs, many synthesis methods have been developed. [20][21][22][23][24] Among these methods, solution casting is a very popular one. This method involves casting a polymer solution onto a lm, followed by phase inversion to remove the solvent and get solid membranes.…”
Section: Introductionmentioning
confidence: 99%